Prevalence of temporo-mandibular disorderd (TMD) among advanced level students in Government Schools in the Colombo Education area - Rasika, G.H.T (My University, 2006)
This is a school based, cross sectional descriptive study design using Cluster sample method, combined with probability proportionate to size (PPS) the sample consisted of 632, A/L students from government schools. A self-administered questionnaire consisting of pretested, modified version of Research diagnostic criteria for temporomandibular disorders (RDC/TMD) and a clinical examination were used to collect data. The prevalence of TMD among AIL students in the Colombo education zone is relatively low. However, it constitutes an emerging oral health problem among adolescents which is woefully underinvestigated in community based studies. Hence, TMD should not be 0terlOOked by oral health care providers in provision of comprehensive oral health care for adolescents, as early detection and appropriate referrals could effectively overcome the deleterious impact of its sufferers.